1975
DOI: 10.2466/pr0.1975.37.3.683
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Situational Variables on Performance of Inbred Mice in Active- and Passive-Avoidance Situations

Abstract: A group of experiments were conducted to assess the interaction between environmental factors and specific genetic loci upon the performance of mice in avoidance learning situations. The performance of all mice was better in passive-avoidance than in active-avoidance situations. The performance of C57BL/6J mice was generally superior to that of DBA/2J mice. C57BL/6J mice usually avoided foot-shocks, while DBA/2J mice attempted to escape them. DBA/2J mice performed poorly in the presence of mild foot-shocks, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
2009
2009

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Although we had only performed 100 trials here, it is unlikely that our observed pattern of results would reverse if additional training was conducted. A survey on the existing literature, however, does not seem to yield a clear consensus on this particular strain difference in avoidance learning, with some reports also failing to identify any clear performance difference (see Bovet et al 1969;Iso and Shimai 1991;Sprott and Stavnes 1975;Stavnes and Sprott 1975b;Vetulani et al 1989;Wahlsten 1972;Weinberger et al 1992). A number of factors have been proposed to account for such apparent inconsistency, including shock intensity (Carran et al 1964;Wahlsten 1972), the modality of the conditioned stimulus (Oliverio 1967), the training protocol (Wimer et al 1968) and the age of the animals (Stavnes and Sprott 1975a).…”
Section: Responsiveness To Systemic Clozapine In Ppi Expressionmentioning
confidence: 90%
“…Although we had only performed 100 trials here, it is unlikely that our observed pattern of results would reverse if additional training was conducted. A survey on the existing literature, however, does not seem to yield a clear consensus on this particular strain difference in avoidance learning, with some reports also failing to identify any clear performance difference (see Bovet et al 1969;Iso and Shimai 1991;Sprott and Stavnes 1975;Stavnes and Sprott 1975b;Vetulani et al 1989;Wahlsten 1972;Weinberger et al 1992). A number of factors have been proposed to account for such apparent inconsistency, including shock intensity (Carran et al 1964;Wahlsten 1972), the modality of the conditioned stimulus (Oliverio 1967), the training protocol (Wimer et al 1968) and the age of the animals (Stavnes and Sprott 1975a).…”
Section: Responsiveness To Systemic Clozapine In Ppi Expressionmentioning
confidence: 90%